THERMOELASTIC DAMPING DEPENDING ON VIBRATION MODES OF NANO BEAM RESONATOR - Hoang, Chu Manh (Communications in Physics, 2016)
The obtainable quality factor for a nano beam resonator is limited due to internal damping such as thermoelastic damping. Therefore, understanding how internal damping varies with the respective resonant modes is very important to design a high performance nanoresonator. In this research, we investigate thermoelastic damping depending on vibration modes of nano beam resonators using finite element method. The study results show that the quality factor of a nanoresonator is lower than at high order modes. The silicon nano beam resonator with the quality factor larger than one million can be achieved by optimizing the dimensions of the resonant beam.